RESPONSIVE WEBDESIGN OF INFORM SYSTEMS (Perner's Contacts, 2015)
In this paper the basics of responsive web, online applicatons and information systems production are described from the view of their display (not only) on mobile devices. A properly designed web application must be ready to adapt its appearance by target devices automatically. Any user should not be limited by resolution or display size and the web content should be accessible and understadable well.
Keywords: responsive webdesign, mobile devices, flexible web, web wireframe